1995
DOI: 10.2118/28691-pa
|View full text |Cite
|
Sign up to set email alerts
|

Tracer-Test Interpretation in Naturally Fractured Reservoirs

Abstract: Summary This paper presents a solution for the inverse problem, or interpretation, to the flow of tracers in naturally fractured reservoirs. The model considers cubic block geometry. The Rosenbrock method for nonlinear regression used in this study, allowed the estimation of up to six parameters for this cubic block geometry. The nonlinear regression for the three cases was carefully tested against synthetical tracer concentration responses affected by random noise, with the objective of simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The applications of tracers to study naturally fractured reservoirs have been the subject of numerous studies (Wagner 1977, Tester et al 1982, Ramirez 1993, Shinta et al 1993, Daltaban et al 1994, Ramirez et al 1994, Sato et al 1994, Zellou et al 1995, Maroongoog et al 1995, Deng et al 1995, Wattenbarger et al 1995, Almeida et al 1996. Despite all these studies (only few cited here), the response of tracers in partially fractured reservoirs is yet to be investigated.…”
Section: Characterization Of Naturally Fractured Reservoirsmentioning
confidence: 99%
“…The applications of tracers to study naturally fractured reservoirs have been the subject of numerous studies (Wagner 1977, Tester et al 1982, Ramirez 1993, Shinta et al 1993, Daltaban et al 1994, Ramirez et al 1994, Sato et al 1994, Zellou et al 1995, Maroongoog et al 1995, Deng et al 1995, Wattenbarger et al 1995, Almeida et al 1996. Despite all these studies (only few cited here), the response of tracers in partially fractured reservoirs is yet to be investigated.…”
Section: Characterization Of Naturally Fractured Reservoirsmentioning
confidence: 99%
“…Ramirez et al investigated the response of the tracer test in matrix fracture medium and tried to estimate fracture opening and also matrix diffusion coefficient in different geometries 7 , 21 . Samaniego and Rodriguez used the tracer data in an observation well to estimate some reservoir parameters in a fractured reservoir using a trial method 22 . Qasem et al showed that parameters such as porosity and permeability and their relationship significantly affect tracer results in fracture-matrix systems 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers used RTA and PTA to characterize the fracture network because production data are available for almost every well. Micro-seismic monitoring is also broadly used in the field to characterize the fracture network during and after the hydraulic fracturing operations. Tracer test is another method commonly used to characterize the fracture network. Each of these three methods has its strengths and limitations. No one method is solid enough to be applicable to all wells, especially when dealing with field data.…”
Section: Introductionmentioning
confidence: 99%